PENGGUNAAN MEDIA POCER “POHON CERITA” UNTUK MENINGKATKAN HASIL BELAJAR MENULIS TEKS CERPEN: SMP NEGERI 2 PAKEM BONDOWOSO - INSIYA (Dewan Pendidikan Bondowoso, 2021)
This research was conducted with the aim of improving the learning outcomes of short story writing. The research was conducted in the form of Classroom Action Research. The respondents of this study were 26 students of class IXA SMP Negeri 2 Pakem. The success indicator is that 85% of students complete the KKM score of 72. The data is obtained through tests as the main data, as well as observation and distributing questionnaires at the end of the cycle as supporting data. The results of the study before the application of smart media, students' learning completeness only reached 46% and after the application of smart media it showed a significant increase of 88%. Based on the results of the study, it can be found that the use of PoCer media is able to improve student learning outcomes in writing short story texts.